INTERACTIVE METHODS IN ENGLISH LESSONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The incorporation of interactive methods requires careful planning and a clear understanding of objectives. Teachers must design activities that align with curricular goals while allowing students to engage meaningfully with the material. Planning involves anticipating learners’ needs, differentiating instruction according to varied proficiency levels, and selecting techniques that encourage both individual accountability and group cooperation. Classroom management also plays a significant role, as the active nature of interactive tasks dem